Draft Annual Plan 1983-84 Union Territory of Dadra and Nagar-Haveli - Planning Commission (Planning Commission, 1983)
Lift Irrigation Schemes has been investigated with the assistance of N.G.R.I. etc. and some small Lift Irrigation Schemes have been completed and others are on hand. However, these Lift Irrigation Schemes are not likely to irrigate more than 5% to 10% land of this territory.
Union Territory of Dadra and Nagar-Haveli, Planning Division Administration